Budaya Jawa dan Islam Sebagai Identitas Indonesia dalam Iklan Djarum 76 Edisi Nikah (Faculty of Communications Science, Dr. Soetomo University, 2018)
Advertising is a form of message to introduce a specific product to the community with the aim that the product can be purchased or consumed by the community. Currently there are a lot of good ads that are broadcast through mainstream media such as television, newspapers and radio broadcasts and also through online media such as youtube, social networking to run on smartphone applications. Various forms of advertising both in terms of packaging, talent, the model is packaged uniquely to provide a persuative message to the audience for the purpose of the ad is met. This paper is a review of a television commercial about the advertisement of a cigarette company Djarum 76 which is packaged in a cultural perspective and cultural context of consumers in the edition of marriage Keywords: Ads, Model, Indonesia, cigarette Djarum 76